The Effect of Yoga Gymnastics Against insomnia among Elderly in Social Institution Tresna Werdha Budi mulia 2 Cengkareng West Jakarta - Hera Hastuti; Iin Andriyani (Universitas Muhammadiyah Tangerang, 2021)
The prevalence of sleep disorders in the elderly is high at around 67%. where 1 of 4 at the age of 60 years experienced serious difficulty sleeping. Sleep disorder is constituted suffering for the Elderly because it deals with a sense of pleasure, happiness, and quality of life. One of the non-pharmacological therapy that could potentially reduce the rate of insomnia is doing yoga. Yoga movement can help patients with insomnia to sleep well because it gives you peace of mind and ultimately help to sleep. This study aims to identify the Effect of Gymnastics Yoga Against Elderly Insomnia in Social Institution Tresna Werdha Budi Mulia 2 Cengkareng West Jakarta. The study design was Quasi Experiment with the design of Pre Test and Post Test One Group Design. Subjects were elderly who have insomnia in Social Institution Tresna Werdha Budi Mulia 2 Cengkareng West Jakarta as many as 13 people with a Total Sampling Technique. The statistical test used is Paired T-Test. The results of the analysis obtained Mean Pre-test 28.62 and after the yoga exercise obtained Mean Post-test 20.15 with paired T-test obtained sig (2-tailed) with p <0.001. The conclusion of this research that there is a significant difference between the Insomnia Pre-test and post-test. It showed the effect the of gymnastics yoga against insomnia among elderly in Social Institutions Tresna Werdha Budi Mulia 2 Cengkareng, West Jakarta. For the next study is suggested to develop an experimental method in the intervention and control groups. Keywords: Insomnia, Elderly, Yoga Gymnastics.